Research of the Collision Problem for Dual Robot Coordination System - Cong Fei; Zhang Qiuju (Jixie chuandong)
Aiming at the problem that the multi-degree-of-freedom dual manipulator may collide in the same workspace,a simplified model of the robot envelope is established. The joint is simplified as a sphere envelope and the connecting rod is simplified as a cylindrical envelope. And the calculation method of the shortest distance between the points and the point to the line segment and the outermost line segments is proposed by detecting the interference between these two simplified models of the double manipulator. The detection algorithm is implemented in VC ++,and the Staubli six-axis dual-robot model is applied to Solid Works for the simulation,the feasibility of this algorithm is verified by the experimental results.